L’image pour déconstruire l’imaginaire à la frontière entre le Tadjikistan et l’Afghanistan - Mélanie Sadozaï (EchoGéo)
Photography provides an opportunity to support a scientific standpoint that views the border between Tajikistan and Afghanistan through the prism of the resources it carries and brings to the actors operating at this border. To do so, photography must be presented alongside other first-hand sources such as numerical data, qualitative interviews and notes drawing on direct observation. This combination of ethnographic methods allows for the elaboration of the narrative depicting a resource-producing border which debunks that of a perceived dangerous border. Images thus become the methodological basis of a written argument.